Nickel-Catalyzed Reductive Allylation of Ketones with Allylic Carbonates - Zhao, Chenglong; Tan, Zhuozhen; Liang, Zhuye; Deng, Wei; Gong, Hegui (Synthesis, 2014)
Nickel-catalyzed efficient umpolung allylation of ketones with allylic carbonates in the presence of zinc powder is developed, which accommodates a variety of allylic and ketone substrates. Although chiral ligand is necessary for the transformation, no enantioselectivity was observed.
Keywords: nickel; catalysis; allylation; umpolung; ketones